Does the interpersonal–Psychological theory of suicide provide a useful framework for understanding suicide risk among eating disorder patients? A test of the validity of the IPTS. Issue 12 (16th August 2016) - Smith, April R.; Dodd, Dorian R.; Forrest, Lauren N.; Witte, Tracy K.; Bodell, Lindsay; Ribeiro, Jessica D.; Goodwin, Natalie; Siegfried, Nicole; Bartlett, Mary
ABSTRACT: Objective: The current study tested whether the Interpersonal–Psychological Theory of Suicide (IPTS) provides a useful framework for understanding elevated suicide rates among individuals with eating disorders (EDs). Method: Based on predictions of the IPTS, we tested whether the combination of thwarted belongingness and perceived burdensomeness was associated with suicidal desire, and whether the combination of thwarted belongingness, perceived burdensomeness, and fearlessness about death was associated with past suicide attempts in an ED sample ( n = 100). We also compared these IPTS constructs in an ED sample versus general psychiatric inpatients ( n = 85) and college students (i.e., non‐clinical comparison group; n = 93). Results: Within the ED sample, no hypothesized interactions were found, but perceived burdensomeness was associated with suicidal desire, and perceived burdensomeness and fearlessness about death were associated with past suicide attempts. The ED and psychiatric samples had greater thwarted belongingness, perceived burdensomeness, and suicidal desire than the non‐clinical comparison group. Discussion: The IPTS constructs of perceived burdensomeness and fearlessness about death appear to explain some facets of suicidality among people with EDs, but overall, support for the IPTS was limited. Future research on EDs and suicidality should look beyond the IPTS and consider other biological and sociocultural factors for suicide. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:1082–1086)